Comparative Study of Literature as a Method of Scientific Research Training of Language and Literature Teachers in the Multicultural Environment of the Republic of Tatarstan - Alsu Khabibullina; Elvira Nagumanova; Oksana Shemshurenko (ARPHA Proceedings, 2019)
The article is devoted to comparative literary studies as a factor in the scientific research training of language and literature teachers in the multi-ethnic environment of the Republic of Tatarstan. The purpose of the article is to determine the place and essence of comparative literary study as a method of research training of future language and literature teachers, to clarify the methods of its representation in the educational process. The study confirmed that in the context of the bi- and multilingual environment, the most valuable is the study of the comparative poetics of the Russian, Tatar and modern Russian-language literature of the Tatars. The paper summarizes the results of experiments aimed at studying the foreign perception of the poem by G. R. Derzhavin "The Harp" and the 66th sonnet by William Shakespeare. It was concluded that the methods of the comparative study of works of Russian and foreign classics among bi-and multilingual Tatar students make it possible to enrich their cultural horizons and cultivate a tolerant attitude towards the world of the "foreigner" in them. The study of the system of special concepts of comparative poetics (multiplicity of literature, aesthetic interference, the principle of complementarities, etc.) as one of the stages of research training of future language and literature teachers contributes to the education of the personality, ready to successfully integrate into the modern sociocultural space in the context of expanding inter-ethnic and inter-linguistic contacts.